STRATEGI PEMASARAN WISATA HALAL - Rahardi Mahardika (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
Halal tourism is one form of culture-based tourism that prioritizes Islamic values ​​and Sharia and of course the ending that is expected is the emergence of superior moral personality as its basic foundation. As a new concept in the tourism industry, of course, sharia tourism requires further development and a more comprehensive understanding of the collaboration of Islamic values ​​that are cooled in halal tourism activities. With the largest Muslim population in the world, Indonesia is one of the largest Halal tourism industry markets in the world and this should be realized by tourism businesses in Indonesia, this is because the development of sustainable Halal tourism will be able to provide a significant economic contribution to all actors involved in it. Online information is currently the main influence in consumer decision making (in this case tourism service users) in almost all major markets, therefore e-marketing is expected to make the pathway as the right product marketing strategy in terms of providing efficient and effective information. for potential consumers who are evenly distributed.